Ethnobotanical Survey on Plants Used to Manage Febrile Illnesses among Herbalists in Casablanca, Morocco - Amal Dagni; Ramona Suharoschi; Simona-Codruta Hegheș; Rodica Vârban; Oana Lelia Pop; Romana Vulturar; Adriana Fodor; Angela Cozma; Abdelaziz Soukri; Bouchra El Khalfi (Diversity, 2023)
Plants have been recognized since antiquity in Morocco as a heritage and a remedy for a variety of ailments with a diverse range of pharmacological effects. The current work is ethnomedicinal research conducted to collect herbalists’ knowledge about plants utilized in traditional medicine to treat febrile illnesses. In Casablanca, Morocco, 105 herbalists provided information. The data were examined using seven quantitative indices: The Fidelity Level (FL), Use Value (UV), Frequency of Citation (FC), Relative Frequency of Citation (RFC), and Informant Consensus Factor (ICF). During the current investigation, twenty-two different species of medicinal plants from eleven families have been reported as being used to treat fevers. The most recommended plant with a high Relative Frequency of Citation (RFC = 0.15) is Dysphania ambrosioides L., which indicates the importance of this species in controlling fever, especially when it is combined with Citrus × limon (L.) Osbeck (RFC = 0.139). Hence, the use of these plants was compared to the literature review. This research contributed to documenting and preserving important Moroccan traditional herbalists’ knowledge about plants used to cure febrile illnesses.